Brand Experience – A Systematic Review and Research Agenda - Sumbly, Yuvika; Siraj, Sadaf (Indian Journal of Marketing, 2019)
Brand experience has been gaining significant value in the marketing literature. Developing memorable, extraordinary brand experience is considered to be a vital strategy for distinguishing the corporate offerings in the competitive marketplace. In order to understand how brand experience has been investigated in the academic literature, this research paper sought to provide a systematic review of brand experience studies in the marketing literature. An extensive review of literature was carried out on brand experience, spread over 45 journals, which yielded an output of 84 conceptual and empirical articles on brand experience spanning from 1997 to 2017. This review found that research on brand experience has gained significant pace in the last six years (2011 - 2017). Antecedents and consequences of brand experience, as examined by various research articles, were also identified and reported in this review.